Gross Anatomical and Morphometrical Studies on the Humerus of Indian Fox (Vulpes bengalensis, Shaw, 1800) - Botlagunta, supriya; Vaddi, Karunasri; Talupuri, Sai urmila; Ankem, Prashanth Babu (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The Indian fox is the smallest wild canid and widely distributed fox species in southern India. The present investigation was performed  on the humeri of four adult Indian foxes to observe their characteristic features. The humerus of the Indian fox was a long, cylindrical  bone with indistinct musculo-spiral groove. The maximum average length of the humerus was 8.925 cm. The shaft had four surfaces.  The anterior and lateral surfaces were separated by an anconeal line that descended from the space between the head and lateral  tubercle and had a distinct teres minor tubercle. The deltoid tuberosity was like a low ridge. The proximal epiphysis consisted of a head  caudally, a neck, a cranio-lateral greater tubercle, and a medial minor tubercle. The intertuberal groove was wide. One nutrient foramen  was observed between the medial face of the lateral tubercle and the head. On the medial surface, the tubercle was absent. The distal  extremity consisted of two condyles and two epicondyles. The lateral and the medial condyles are called capitulum humeri and trochleo  humeri, respectively. The trochlea is articulated with the trochlear notch of the ulna to give more stability to the elbow joint. An oval  supratrochlear foramen connected the coronoid and olecranon fossae. The supracondyloid foramen was absent.
Keywords: Anconeal line; Deltoid tuberosity; Humerus; Indian fox; Morphometry